Effects of Light-at-Night on the Rat Liver – A Role for the Autonomic Nervous System - Opperhuizen, Anne-Loes; Foppen, Ewout; Jonker, Martijs; Wackers, Paul; van Faassen, Martijn; van Weeghel, Michel; van Kerkhof, Linda; Fliers, Eric; Kalsbeek, Andries (Frontiers in Neuroscience, 2019)
Exposure to light at night (LAN) has been associated with serious pathologies, including obesity, diabetes and cancer. Recently we showed that 2 hours of LAN impaired glucose tolerance in rats. Several studies have suggested that the autonomic nervous system (ANS) plays an important role in communicating these acute effects of LAN to the periphery. Here, we investigated the acute effects of LAN on the liver transcriptome of male Wistar rats. Expression levels of individual genes were not markedly affected by LAN, nevertheless pathway analysis revealed clustered changes in a number of endocrine pathways. Subsequently, we used selective hepatic denervations (sympathetic (Sx), parasympathetic (Px), total (Tx, i.e., Sx plus Px), sham) to investigate the involvement of the ANS in the effects observed. Surgical removal of the sympathetic or parasympathetic hepatic branches of the ANS resulted in many, but small changes in the liver transcriptome, including a pathway involved with circadian clock regulation, but it clearly separated the four denervation groups. On the other hand, analysis of the liver metabolome was not able to separate the denervation groups, and only 6 out of 78 metabolites were significantly up- or downregulated after denervations. Finally, removal of the sympathetic and parasympathetic hepatic nerves combined with LAN exposure clearly modulated the effects of LAN on the liver transcriptome, but left most endocrine pathways unaffected. Conclusion: One-hour light-at-night acutely affects the liver transcriptome. Part of this effect is mediated via the nervous innervation, as a hepatectomy modulated and reduced the effect of LAN on liver transcripts.